Settlement Behavior Analysis of Adjacent Existing Buildings Induced by Foundation Pit Construction in River Basin - Yanlu Zhao; Mingrui Cao; Zhigang Guo; Lifeng Zhang; Erdi Abi (Buildings)
The Yellow River Basin features a unique geographical environment with challenges like seawater erosion and soft soil. In this context, the construction of foundation pits can significantly impact the settlement of adjacent structures. Grounded in a real-world project, this study employs the finite element software Midas GTS to construct a 3D interaction model between foundation pit excavation and nearby buildings. Through this model, we analyze the settlement patterns of adjacent buildings influenced by variables such as foundation soil strength, slope gradient, and construction sequence. By integrating orthogonal experimental design and range analysis, we identify the sensitive factors affecting the settlement deformation and stability of foundation pits. Our analysis reveals that among the factors significantly influencing settlement deformation at the foundation pit base, groundwater levels and internal friction angles are the most critical. Slope gradient and soil cohesion also play substantial roles, whereas the compressive modulus of soil shows relatively less impact. However, a comparison with actual engineering data indicates that groundwater factors considerably affect slope deformation, underscoring the necessity for stringent control of groundwater level fluctuations.